2018
DOI: 10.1017/ice.2018.50
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Isolation on Healthcare Worker Contact and Compliance With Infection Control Practices in Nursing Homes

Abstract: OBJECTIVETo directly observe healthcare workers in a nursing home setting to measure frequency and duration of resident contact and infection prevention behavior as a factor of isolation practiceDESIGNObservational studySETTING AND PARTICIPANTSHealthcare workers in 8 VA nursing homes in Florida, Maryland, Massachusetts, Michigan, Washington, and TexasMETHODSOver a 15-month period, trained research staff without clinical responsibilities on the units observed nursing home resident room activity for 15-30-minute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…The low rate of hand hygiene adherence (36.7%) evident in our study was within the 15%-54% range reported by other studies in similar settings. 1,2,13,14 Hand hygiene rates were particularly low for CNAs and PT/OT staff. Hand hygiene in NFs poses specific challenges due to limited staff training, low HCP-to-patient ratio, and the need for HCP to provide care in a setting that serves as a community living environment with potential for frequent spontaneous, unplanned interactions with patients.…”
Section: Discussionmentioning
confidence: 99%
“…The low rate of hand hygiene adherence (36.7%) evident in our study was within the 15%-54% range reported by other studies in similar settings. 1,2,13,14 Hand hygiene rates were particularly low for CNAs and PT/OT staff. Hand hygiene in NFs poses specific challenges due to limited staff training, low HCP-to-patient ratio, and the need for HCP to provide care in a setting that serves as a community living environment with potential for frequent spontaneous, unplanned interactions with patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although barrier precautions were required for direct care within the room, compliance was low, with 58% of HCP using gloves and 34% using gowns. 7 The frequency of contact with the patient or environment within the room was not monitored, so numbers between these 2 studies are not directly comparable. Therefore, we could not estimate the total amount of contact between residents and staff inside of rooms versus outside the rooms, but direct contact with staff was considerable in common areas, especially in rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Facility-level PPE adherence. Adherence to PPE use by healthcare staff in nursing homes has been less than optimal before the COVID-19 pandemic [36] . In the beginning of the pandemic, initial CMS surveys (during the week of March 30, 2020) found that 25% of inspected facilities failed to demonstrate proper use of PPE [37] .…”
Section: Methodsmentioning
confidence: 99%